Clinical Aniseikonia in Anisometropia and Amblyopia. Issue 1 (20th November 2020) - South, Jayshree; Gao, Tina; Collins, Andrew; Lee, Arier; Turuwhenua, Jason; Black, Joanna
Purpose: Clinically, aniseikonia (a perceived difference in shape and image size between the eyes) is often neglected in anisometropic amblyopia due to assumed measurement difficulties. Therefore, we currently lack evidence on whether correction of aniseikonia is beneficial. This study aimed to determine whether subjective aniseikonia is measurable in anisometropia with or without amblyopia. Methods: Participants (15–52 years) with Anisometropic Amblyopia (n = 7), Anisometropia without amblyopia (n = 6) and Isometropic Controls (n = 6) were recruited. Subjective aniseikonia was measured using three clinical techniques: Robertson Technique (RT) (penlight and Maddox rod), Aniseikonia Inspector Version 3 (AI3), and the New Aniseikonia Test booklet (NAT), and a psychophysical adaptive method, the Contrast-balanced Aniseikonia Test (CAT), where dichoptic contrast adjustments compensate for any suppression. Results: Eighteen participants completed all tests, one Anisometropic Amblyopia participant could only complete the CAT and NAT due to fusion loss. The Anisometropic Amblyopia group exhibited the most aniseikonia (range –1.50–+10.50%) followed by Anisometropic Controls (range –3.30–+4.50%) and Isometropic Controls (range –1.50–+3.28%). There was a significant trend of more subjective aniseikonia with increasing amounts of anisometropia across all four tests (AI3 r = 0.630, p = 0.005; NAT r = 0.542, p = 0.017; RT r = 0.499, p = 0.035; CAT r = 0.440, p = 0.059. Bland Altman analysis demonstrated clinically significant levels of variability between the tests. Conclusions: Subjective aniseikonia can be reliably measured in patients with anisometropia and suppression. Subjective aniseikonia measurement is recommended as four of the most commonly used clinical tests did not support the 1% per dioptre rule of thumb.